2009
DOI: 10.1016/j.atherosclerosis.2009.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging of atherosclerotic plaque activity and composition using FDG-PET/CT and MRI in carotid and femoral arteries

Abstract: Purpose To evaluate the relationship between atherosclerotic plaque inflammation, as assessed by FDG-Positron Emission Tomography/Computed Tomography (FDG-PET/CT), and plaque morphology and composition, as assessed by magnetic resonance imaging (MRI), in the carotid and femoral arteries. Materials and methods Sixteen patients underwent FDG-PET/CT and MRI (T2 weighted (T2W) and Proton density weighted (PDW)) of the carotid and femoral arteries. For every image slice, two observers determined the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
106
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 24 publications
(25 reference statements)
9
106
1
2
Order By: Relevance
“…No correlation was found between FDG uptake and plaque thickness, area or smooth muscle staining. It has since been shown that FDG can quantify inflammation in the aorta, iliac and peripheral arteries, with excellent short-term and interobserver reproducibility [49][50][51][52]. This has proved important in the search for quantitative measures of inflammation that can be used to test the impact of new therapies.…”
Section: Clinical Studies With Fdg-petmentioning
confidence: 99%
See 1 more Smart Citation
“…No correlation was found between FDG uptake and plaque thickness, area or smooth muscle staining. It has since been shown that FDG can quantify inflammation in the aorta, iliac and peripheral arteries, with excellent short-term and interobserver reproducibility [49][50][51][52]. This has proved important in the search for quantitative measures of inflammation that can be used to test the impact of new therapies.…”
Section: Clinical Studies With Fdg-petmentioning
confidence: 99%
“…Arterial uptake in one vascular region correlates strongly with its anatomical pair, and more strongly with neighbouring regions than more distally. Plaques with high-risk features on MRI (large lipid core [49] or intraplaque haemorrhage [63]) or ultrasound [64,65] (echolucency) have higher FDG than more stable phenotypes. Aortic uptake has been shown to correlate with circulating biomarkers matrix metalloproteases 1, 3 and 9 [54,66], and an inverse correlation has been reported with the atheroprotective biomarkers adiponectin and plasminogen activator inhibitor 1 [54,66].…”
mentioning
confidence: 99%
“…Indeed, this combined approach has now been applied to carotid plaque imaging (12,13). However, the findings have been conflicting with respect to the relationship between uptake on PET and anatomic imaging: lipid-rich necrotic core plaques demonstrated higher 18 F-FDG uptake than calcified or collagen plaques in one study (12), but no strong correlations between 18 F-FDG uptake and the CT-or MRI-assessed composition of the plaques existed in another (13). Moreover, gold standard histologic comparison was unavailable for either of these studies.…”
mentioning
confidence: 99%
“…It has been shown to be reproducible, with low levels of inter-observer and short-term variability [29]. In carotid imaging, high FDG uptake correlates well with features of vulnerability noted on other modalities, for example, echolucency on ultrasound [30] and lipid rich cores on MRI [31]. Vascular FDG PET is being used to investigate the excess cardiovascular risk associated with other chronic inflammatory diseases such as HIV [32], chronic obstructive pulmonary disease [33] and rheumatoid arthritis [34].…”
Section: Imaging Inflammation Using Fdg Petmentioning
confidence: 99%